Workplace digital transformation: Impact of employees’ autonomy and relatedness to employees’ intention actively support digital transformation - Maghrifani, Dila; Fadli, Adennia Oktaviana; Ardekani, Aref Mahdavi (Universitas Sebelas Maret, 2022)
The existence of the Covid-19 pandemic has significantly changed the world order to become completely digital. Therefore it is necessary to have the desire to continue to change with the times, whether for each individual or the company. Before carrying out digital transformation in the workplace, companies need to think about how their employees can actively support digital transformation. This research examines several factors, such as autonomy, relatedness, and performance, in actively fostering employee intentions to support digital transformation in the workplace. Using the cross-sectional method, there were 95 respondents from employees in the banking sector in Surakarta and its surroundings. In general, this study found that autonomy, relatedness, and performance can increase employee intention to support digital transformation in the workplace. This research is expected to provide insights for companies to examine what factors are needed to prepare for workplace digital transformation. In addition, this research is also expected to add to the literature for up-to-date research on digital transformation in Indonesia.